2013
DOI: 10.1080/10509674.2013.782773
|View full text |Cite
|
Sign up to set email alerts
|

Family Connections: The Importance of Prison Reading Programs for Incarcerated Parents and Their Children

Abstract: This article introduces a successful reading program, FamilyConnections, for incarcerated parents and their children. A comprehensive review of the literature supports the need to implement prison programs from an ecological perspective, in which the needs of inmates and their families are considered. More specifically, the benefits of directing resources toward the establishment of reading programs in prisons and jails for inmates and their children are discussed. The Family Connections program is aimed at im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Our findings suggest, certainly in the short term, that visitation programs like MCVP have negative effects on children’s wellbeing and development. This finding is contradicted by research that suggests visitation is beneficial for children (Blumberg and Griffin, 2013; Block and Potthast, 1998; Snyder, 2009; Trice and Brewster, 2004), as well as some outcome research that shows maternal incarceration is largely inconsequential for children, particularly among those whose mothers are most likely to experience incarceration (Turney and Wildeman, 2015). There are several plausible reasons for this apparent contradiction.…”
Section: Resultsmentioning
confidence: 89%
“…Our findings suggest, certainly in the short term, that visitation programs like MCVP have negative effects on children’s wellbeing and development. This finding is contradicted by research that suggests visitation is beneficial for children (Blumberg and Griffin, 2013; Block and Potthast, 1998; Snyder, 2009; Trice and Brewster, 2004), as well as some outcome research that shows maternal incarceration is largely inconsequential for children, particularly among those whose mothers are most likely to experience incarceration (Turney and Wildeman, 2015). There are several plausible reasons for this apparent contradiction.…”
Section: Resultsmentioning
confidence: 89%
“…A myriad of research describes the benefits for children of regular high-quality shared reading even with caregivers outside the family (e.g., teachers, librarians, and volunteers). Shared reading promotes children's early language growth (Reese and Cox, 1999;Fitzgerald et al, 2018) and preliteracy skills (Foorman et al, 2002;Brown, 2014), assists children's socio-emotional development and communication skills (Bergin, 2001;Aram and Shapira, 2012), and helps establish a bond between caregivers and children (Blumberg and Griffin, 2013). Dialogic reading intervention where adult readers are encouraged to actively prompt children with story-related questions as they read-aloud have been repeatedly shown to improve the language comprehension, vocabulary, and print awareness among children who are read to by adult volunteers (e.g., Fitzgerald et al, 2018).…”
Section: Shared Reading and The Benefits For Childrenmentioning
confidence: 99%
“…While shared reading supports children's early language development and socio-emotional development, research has also revealed that shared reading can help establish a bond between the child and the reader (Bus and van Ijzendoorn, 1997;Lariviere and Rennick, 2011;Blumberg and Griffin, 2013). Seden (2008) found that reading children's books with a child supports positive parent-child relationships for low-income and stressed parents by enhancing parents' abilities to tend to their child's needs and empathize with their child more deeply.…”
Section: Shared Reading and The Benefits For Both Children And The Readersmentioning
confidence: 99%
“…For fathers who are currently incarcerated, physical confinement makes it impossible for them to participate in any school-based activities. Confinement also makes it quite difficult, although not impossible (see Lombardi 2004; Marte 2015), to engage in home-based types of schooling activities, such as helping with homework or reading with their children (e.g., during visitation or through prison family reading programs; Blumberg and Griffin 2013). Additionally, recent theories regarding formerly incarcerated populations provide insight into how a previous incarceration spell may affect parental involvement in schooling even after release.…”
Section: Paternal Incarceration and Parental Involvement For School-amentioning
confidence: 99%